THE EFFECT OF GREEN TEA LEAF EXTRACT ON SPATIAL MEMORY FUNCTION AND SUPEROXYDE DISMUTASE ENZYME ACTIVITY IN MICE WITH D-GALACTOSE INDUCED DIMENTIA - Ainun Rahmasari Gumay; Saekhol Bakri; Astika Widy Utomo (Sains Medika, 2017)
Background: Oxidative stress and inflammation play an important role in pathogenesis of brain aging and neurodegenerative diseases such as Alzheimer. Green tea has been shown to have antioxidant, anti-inflammatory, anticancer, and neuroprotective activity. Objectives: to determine the effect of green tea extract on spatial memory function and superoxide dismutase enzyme activity in mice with D-galactose induced dementia